Building Green Process Innovation Performance in Batik Tulis Lasem - Riyadi, Riyadi; Nanang Adie Setyawan; Suwardi, Suwardi; Saptianing, Saptianing; Andi Setiawan (Cita konsultindo, 2023)
Research on business continuity is an interesting topic to investigate, given the intense competition in the business world. The purpose of this study is to develop Green Process Innovation Performance from Green Strategic Intentions with the help of Intervening Variables, namely Green Intellectual Capital consisting of Green Human Capital, Green Organizational Capital, and Green Relational Capital. The population that became the subject of this study were MSME business actors engaged in Batik Tulis Lasem in Rembang Regency. The sampling method used is the census method, and the number of samples used is 115 respondents, which is part of the total population. The results of the model generated from this study are expected to make a positive contribution to the UMKM players of Batik Tulis Lasem in an effort to maintain the continuity and sustainability of their business, especially in the environmental aspect. The results of this study can also be articulated in the form of suggestions for management and formulation of scientific articles, as well as the development of measurement instruments. The managerial advice generated from this research can be useful for local governments in formulating policies and programs aimed at supporting the continuity of entrepreneurs, especially after the COVID-19 pandemic.